Development of Pontianak Port: Supporting and Inhibiting Factors, 1980-2012 - Amellia, Gita; Susilowati, Endang (Diponegoro University, 2023)
This This article discusses the development of Pontianak port from 1980 to 2012. Pontianak Port is an important port because, in addition to being a shipping port, it is also a loading and unloading port for commodities such as rubber, tengkawang, and wood. This research uses historical methods to describe the factors that influenced the development of the Pontianak Port. The results show that Pontianak Port does not stand alone and is an inseparable part of the development of other sectors. The development of industries such as rubber in West Kalimantan, adequate port facilities, the construction of the Trans Kalimantan Road which facilitated the delivery of goods from the interior to the port, and the development of Ketapang port became important factors in the development of Pontianak Port. However, in its development, several factors hinder the development of Pontianak Port such as silting of the port entrance and also dredging the pond.